Albert Morris Cohen papers - Cohen, Albert Morris, 1883-1959.
Correspondence, journals, reports, circulars, photographs, and scrapbooks relating to Cohen's service with the U.S. Naval Aviation Corps during World War I and to his duties aboard the U.S. transport ship George Washington and the U.S. battleship Louisiana. Correspondents include Cohen's father, Charles J. Cohen; his mother, Clotilda Florance Cohen; his brother, Henry Barnet Cohen; and his sister, Eleanor C. Hillman.
Naval officer.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Cohen, Charles J. -- 1847-1927 -- Correspondence; Cohen, Clotilda Florance -- Correspondence; Cohen, Henry Barnet -- Correspondence; Hillman, Eleanor C. -- Correspondence; George Washington (Transport ship); Louisiana (Battleship); United States. -- Naval Aviation Corps; United States. -- Navy -- Aviation; United States. -- Navy -- History -- World War, 1914-1918.; United States. -- Navy -- Officers; World War, 1914-1918 -- Aerial operations, American; World War, 1914-1918 -- Naval operations, American; Naval officers